The effects of web-based progressive muscle relaxation exercise on perceived stress and anxiety levels of nursing students who were in clinical practice for the first time - a randomized controlled trial - Ciftci, Bahar; Turan, Gulcan Bahcecioglu; Sarialioglu, Arzu (Srpsko Lekarsko Drustvo, 2021)
Introduction/Objective It is reported that during the education process, uncontrollable long-term stress affects professional identity development and health of nursing students negatively.The effects of web-based progressive muscle relaxation exercises on perceived stress and anxiety levels of nursing students who were in clinical practice for the first time were analyzed in the present study. Methods The present study used a randomized controlled design.The study was carried out at a state university in Turkey. A total of volunteering 66 nursing students (36 in the control and 30 in the intervention group) in clinical practice for the first time who were studying during the 2021-2022 academic year were included in the sample. Intervention group students performed 36 sessions of progressive muscle relaxation exercise three days a week for 12 weeks. The data were collected by using the Sociodemographic Characteristics Form, State-Trait Anxiety Inventory (STAI), and Perceived Stress Scale (PSS). Results In comparing post-test mean scores of intervention and control group, PSS and STAI total mean scores of the intervention group were found to be statistically significantly lower than those of the control group (p < 0.05). Conclusion Progressive muscle relaxation exercise was found to reduce perceived stress and anxiety in nursing students who were in clinical practice for the first time.
Keywords: anxiety; nursing student; stress; progressive muscle relaxation; randomized controlled study